5-Year Follow-up of Active Tuberculosis Development From Latent Infection in Rural China. (28th June 2019) - Xin, Henan; Zhang, Haoran; Yang, Shumin; Liu, Jianmin; Lu, Wei; Bai, Liqiong; Cao, Xuefang; Feng, Boxuan; Jin, Qi; Gao, Lei
Abstract: A 5-year follow-up study found declining disease development rates from latent tuberculosis infection. In the latter 3 years, the incidence, per 100 person-years, was 0.26 for interferon-γ release assay positives and 0.19 for tuberculin skin test positives (P = .28). In addition, all round have been checked.